FORMULATION AND EVALUATION OF GOLDEN SEA CUCUMBER (STICHOPUS HERRMANNI) ORAL SUSPENSION - Fauzi, Ahmad; Santoso, Broto; Hidayatullah, Muhammad Haqqi; Zafarani Azzuhra, Alifia; Ahsaninnisa, Azizah (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
The Golden Sea Cucumber (Stichopus herrmanni) is widely recognized for its high protein and collagen content, making it valuable for medicinal applications, such as wound healing and tissue regeneration. The present study focused on formulating an oral suspension of sea cucumber extract, assessing its stability, and determining its protein content. Extraction was performed using a boiling method with distilled water to yield a protein-rich extract, which was then formulated into four suspension formulas (Formula 1, 2, 3, and 4) using pharmaceutical-grade excipients, including sorbitol, sodium CMC, and sodium benzoate. Protein quantification was conducted using the Biuret method with Bovine Serum Albumin (BSA) as a standard and analyzed using UV-Vis spectrophotometry. Stability testing over 1, 3, and 6 months was used to evaluate pH, viscosity, and sensory characteristics (odor, color, and taste). Among the four formulations, formula 4 demonstrated the highest stability, maintaining optimal homogeneity, sensory attributes, and pH, along with the highest protein concentration (8.10 mg/mL. These results highlight Formula 4 as the most promising because of its superior stability and protein content. This study underscores the challenges of long-term stability in protein-based suspensions, suggesting the need for further research into advanced excipient selection and encapsulation techniques to protect sensitive proteins. Overall, this research supports the potential use of marine-derived bioactive compounds in pharmaceutical applications, paving the way for sustainable healthcare and cosmetic products. Keywords: golden sea cucumber, Stichopus herrmanni, oral suspension formulation, stability test